Effect of disc materials on brake emission during moderate-temperature braking. (November 2021) - Seo, Hyungjo; Park, Jongsung; Kim, Yun Cheol; Lee, Jung Ju; Jang, Ho
Abstract: Disc material effects on particle emission were investigated under moderate braking conditions using grey iron discs with different microstructures and a ceramic disc. The results demonstrate that brake emissions are strongly affected by disc hardness and the iron transferred to the pad surface. The transferred iron increased brake emissions due to the reduced cohesive strength of the plateaus on the pad surface. The grey iron microstructure also affected the ultrafine particle concentration owing to the graphite flakes. Conversely, the ceramic disc exhibited significantly lower brake emissions due to high wear resistance and no iron transfer to the pad surface. Highlights: Brake emission is inversely proportional to the surface hardness of brake discs. Grey iron discs aggravate the pad wear due to the iron transferred to the pad surface. The cohesive strength of pad contact plateaus decreases with transferred iron content. Graphite flakes in grey iron considerably contribute to nanosized particle emission.